THE INFLUENCE OF THE EMPLOYEE’S ATTRIBUTION TOWARDS HUMAN RESOURCES MANAGEMENT POLICIES TO EMPLOYEE’S MOTIVATION AND ORGANIZATIONAL COMMITMENT IN PKU MUHAMMADIYAH YOGYAKARTA HOSPITAL - Hening Pratiwi; Djoko Wahyono; Edi Prasetyo Nugroho (Faculty of Pharmacy, Universitas Gadjah Mada)
There are some factors that influence human resources management, they are the employee’s attribution, working motivation, and organizational commitment. The purpose of this research is to determine the influence of the employee’s attribution toward human resources management policies to employee’s motivation and organizational commitment in PKU Muhammadiyah Yogyakarta Hospital. This research used questionnaire to 51 employees as subjects and had been working at least 1 year in PKU Muhammadiyah Yogyakarta Hospital. The questionnaires that used in this research consists of questionnaire for employee’s attribution toward human resources management policies, working motivation questionnaire, and organizational commitment questionnaire. To test validity and realibility used 25 respondents, then analyzed with regression analysis to determine the influence of the employee’s attribution toward human resources management policies to working motivation and organizational commitment used SPSS 17 for windows program for analyzing data. The results showed that employee’s attribution toward human resources management policies has positive influence 94,9 % to motivation employees with regression equation Y = 6,425 + 0,967X, employee’s attribution toward human resources management policies has positive influence to organizational commitment 92,6% with regression equation Y=10,133 + 0,735X, and working motivation correlates positively with organizational commitment with r 0,980.Keywords : Employee’s attributions, working motivation, organizational commitment